Milk Satisfied as An Alternative for Food Diversification for Banten Food Security - Dede Agus; Nuryati Solapari; Muslih, Muhamad (Faculty of Law, University of Mataram, 2025)
The dependence of Indonesian society on rice is still ingrained and difficult to replace, let alone abandon. In addition, the recent situation and conditions show a decline in rice production in several regions in Indonesia. This has an impact on the food security of the Indonesian people, especially the people living in Banten. One of the typical foods’ natives to Banten is Milkfish Satay. Milkfish Satay can be an alternative food diversification to avoid the dependence of the Banten people on consuming rice. The legal issue in this study is whether milkfish satay can be an alternative food diversification for the Banten people and how to campaign for a reduction in their rice consumption. According to the researcher, the purpose of the study is to find out the latest conditions of rice production in Banten so that they can find out how important food diversification is for the Banten people today. The researcher argues that the long-term goal of this study is for the Banten community to consume more than just one staple food because many alternative staple foods can be used as staple foods by following the concept of food diversification according to Law Number 18 of 2012 which discusses food and Government Regulation Number 68 of 2002 which discusses Food Security. Then the researcher uses a method to achieve these goals, namely the normative sociological and normative juridical legal research method, which is descriptive-analytical using primary and secondary data sources which are analysed by the researcher qualitatively.